Experimental Study on Stabilization Subgrade Soil Soft with Fine Concrete Residue - Sara del Rocio Ochoa Averos; Julio César Bizarreta-Ortega (ESPOCH Congresses, 2021)
Abstract The reuse of construction and demolition waste (CDW) is a sustainable practice that in recent years has been investigated with great intensity around the world. Concrete waste are a part of the CDW, whose application in pavements is still under development. In this context, this article aims to evaluate the use of concrete fine fraction waste (CW-fine), with particles smaller than 2mm, to improve a soft subgrade soil of residual origin. For this purpose, their physical characteristics, the compaction and California Bearing Ratio (CBR) have been analyzed, both of the natural soil and of the mixtures with CW-fine in proportions of 20, 40 and 60% by weight. The results show that when adding CW-fine, Atterberg limits, specific gravity of solid particles, optimum moisture content and expansion, decrease; while the maximum dry density and CBR increase. The expansion and CBR results of the soil mixture with CW-fine show acceptable values for the subgrade reinforcement, in accordance with Brazilian paving standards.